Peningkatan Kemampuan Mengenal Angka dengan Menggunakan Metode Snowball Throwing bagi Anak - Muntari, Sri (Program Studi Pendidikan Guru Raudlatul Athfal, UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the ability to recognize the numbers of students in Group A TK Widya Tama Cabak and the use of the snowball throwing method can improve the ability to recognize the numbers of students in Group A TK Widya Tama Cabak Academic Year 2016/2017. The subjects studied were 31 students of group A TK Widya Tama Cabak. Data collection techniques using observation, interview, and documentation techniques. The data analysis technique uses descriptive qualitative and comparative. The research procedure consists of two cycles, namely: cycle I and cycle II, with each of the four stages of each cycle, namely: (1) planning the action (planning), (2) implementing the action (acting), (3) observing ( observing), and (4) reflection (reflecting). The results of the study concluded that: (1) Ability to recognize the numbers of students in Group A Widya Tama Cabak Kindergarten in the 2016/2017 Academic Year before the action was taken, namely at the pre-cycle level was still low. The ability to recognize the number of children included in the BSB and BSH categories in the pre-cycle was only 10 children (32.26%). (2) The use of the snowball throwing method can increase the ability to recognize the numbers of students in Group A TK Widya Tama Cabak for the 2016/2017 Academic Year. This is evidenced from: (a) Increasing the ability to recognize the number of children included in the BSB and BSH categories starting from the pre cycle, cycle I to cycle II, namely: the new pre cycle of 32.26%, the first cycle becomes 64.52% and the cycle II to be 90.32%. (b) Increasing the average value of the ability to recognize the number of children starting from the pre-cycle, the first cycle to the second cycle, namely: pre-cycle of 11.61 which included the Emerging (MM) category, cycle I increased to 13.16 which included the category Developing according to Expectations (BSH) and the second cycle the score increased again to 15.39 and included the Expectation Development Expectation (BSH) category.